Analysis of Pasombahan Kreasi Dance Movements in Bangkinang Sub-District Kampar Regency City, Riau Province - Laras Tri Andini; Darmawati (Universitas Negeri Padang, 2024)
The purpose of this study was to find and describe the Pasombahan Kreasi Dance Motion Analysis in Bangkinang Kota District, Kampar Regency, Riau Province. This type of research is qualitative, using descriptive methods. The instrument in this research is the researcher himself and is assisted by supporting instruments such as stationery, flash discs, and mobile phones. Data collection techniques are done through literature study, observation, interviews, and documentation. The steps in analyzing data include data reduction, data presentation, and conclusion drawing. The results showed that the movements in Pasombahan Dance consisted of four names for various movements, namely sombah, punte tali bowuok, klenjek, and sendeng. But in each part of the movement, there are several more parts with a total of 17 motion motifs, but with different counts. Pasombahan dance analysis is seen from the perspectives of space, time, and energy. The element of space in each Pasombahan dance uses a dominant straight line and a right diagonal line. The dominant volume in Pasombahan Dance is medium and small, facing towards the front and towards the front right diagonal. The level contained in the Pasombahan Dance is medium and high in each motion motif, with the focus of the head towards the front and towards the hand movements. The time aspect of this Pasombahan dance has a slow tempo in the sombah movement, while the rest uses a fast tempo. As for the energy element, the ending increases the intensity.